2023
DOI: 10.1021/acsami.3c06178
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cellulose Aerogel Reinforced with In Situ-Assembled Cellulose Nanofibers for Building Cooling

Abstract: The development of new structural materials for passive daytime radiative cooling (PDRC) of buildings will significantly reduce global building energy consumption. Cellulose aerogels are potential PDRC materials for building cooling, but the cooling performance and mechanical strength of cellulose aerogels are considered as challenges for their practical applications. Herein, a bio-inspired hierarchically structured cellulose aerogel (HSCA) was fabricated through an assembly strategy assisted by a high-voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As shown in Figure b, it can be demonstrated that GP and PS foam have similar thermal insulation properties, while the thermal insulation properties of BN/GP are slightly lower than those of GP and PS foams, due to the doping of BN, which improves the thermal conductivity of the composite aerogel . However, the BN nanoparticles are mainly concentrated on the surface because of the gravity effect during the preparation process, which limits the further improvement of the thermal conductivity of BN/GP; meanwhile, the obvious temperature difference from the top and the bottom of the asymmetric BN/GP aerogel cooler also confirmed that it still has outstanding thermal insulation properties and can inhibit heat-transfer effect as shown in Figure S6, which is expected to expand applications as building energy-saving materials …”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure b, it can be demonstrated that GP and PS foam have similar thermal insulation properties, while the thermal insulation properties of BN/GP are slightly lower than those of GP and PS foams, due to the doping of BN, which improves the thermal conductivity of the composite aerogel . However, the BN nanoparticles are mainly concentrated on the surface because of the gravity effect during the preparation process, which limits the further improvement of the thermal conductivity of BN/GP; meanwhile, the obvious temperature difference from the top and the bottom of the asymmetric BN/GP aerogel cooler also confirmed that it still has outstanding thermal insulation properties and can inhibit heat-transfer effect as shown in Figure S6, which is expected to expand applications as building energy-saving materials …”
Section: Resultsmentioning
confidence: 98%
“…32 Therefore, it is crucial to develop and adopt environmentally friendly, biobased PDRC materials with efficient cooling properties. 33−35 For example, renewable materials such as gelatin 36,37 and cellulose 38 are expected to be promising PDRC candidates due to their diversity, accessibility, biocompatibility, and biodegradability. 39 During the day, the radiative cooler provides effective subambient cooling that meets the real needs of the population.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These include nanocomposite films, metamaterials, multilayer photonic structures, and coatings. Although significant progress has been made in improving solar reflectance and increasing the emissivity of atmospheric transparent windows to optimize cooling efficiency, the overuse of nonrenewable materials remains a pressing issue . Therefore, it is crucial to develop and adopt environmentally friendly, biobased PDRC materials with efficient cooling properties. For example, renewable materials such as gelatin , and cellulose are expected to be promising PDRC candidates due to their diversity, accessibility, biocompatibility, and biodegradability …”
Section: Introductionmentioning
confidence: 99%
“…In construction, cellulose-based aerogels can serve as structural materials for passive daytime building radiation cooling. In [17], the authors scrutinized the fabrication of such a material. The results indicated that the synthesized aerogels enable the attainment of a maximum cooling temperature of 7.2 • C and exhibit an axial compression strength of 1.9 MPa.…”
Section: Introductionmentioning
confidence: 99%